Acute proximal left anterior descending coronary artery occlusion presenting with Normal ECG: A case report. Issue 6 (5th September 2022) - Hu, Yuecheng; Jin, Dongxia; Liu, Chunwei; Zhang, Rui; Zhou, Shiying; Wang, Le; Cong, Hongliang
Abstract: The middle‐aged male was diagnosed with "acute anterior wall myocardial infarction" based on clinical symptoms, laboratory examination, and coronary angiography (CAG), but his ECG showed no significant change in QRS wave or ST‐T within 6 h of admission. Thus, a perfect explanation with the existing theory is difficult, and only the case is presented here. Abstract : The middle‐aged male was diagnosed with "acute anterior wall myocardial infarction" based on clinical symptoms, laboratory examination, and coronary angiography (CAG), but his ECG showed no significant change in QRS wave or ST‐T within 6 h of admission. Thus, a perfect explanation with the existing theory is difficult, and only the case is presented here.